Effects of acute and chronic exercise on fat metabolism - Martin, W. H. (Exercise and Sport Sciences Reviews, 1996)
Fatty acids are an important source of energy for skeletal muscle contraction, particularly during exercise of mild-moderate intensity, prolonged duration, and in the fasting state. Plasma FFA transported from remote adipose tissue stores and triglycerides contained within skeletal muscle fibers are the major sources of these fatty acids. The relative contribution of each source is dependent on the mode, intensity, and duration of exercise and on training status. Plasma FFA oxidation is directly related to the rate of lipolysis in adiopose tissue. The most potent stimulants of the latter are the catecholamines, but a lower plasma insulin concentration during exercise also plays a contributory role. In contrast, intramuscular triglyceride hydrolysis appears to be mediated entirely by beta 2-adrenergic stimulation. Endurance training substantially enhances fatty acid oxidative capacity in skeletal muscle and increases the proportion of energy derived from fatty acid oxidation during exercise. In addition, the sympathoadrenal response to exercise is markedly blunted in the trained state. Studies conducted in our laboratory indicate that plasma FFA and glycerol concentrations and whole body FFA uptake and oxidation are all decreased during moderate-intensity exercise at the same absolute work rate after physical conditioning, probably because of the reduction of sympathoadrenal activity. However, the lipolytic response to catecholamines also is enhanced in trained subjects. Perhaps as a consequence, the magnitude of the decrease in lipolysis and plasma FFA oxidation is less than the decrement in sympathoadrenal activity in the same individuals during exercise in the trained state. Other investigations were conducted in our laboratory to determine the source of the additional fatty acids oxidized in physically conditioned subjects. These studies demonstrated that during moderate-intensity exercise at the same absolute work rate, depletion of triglycerides from within skeletal muscle fibers was twice as great after, as opposed to, before training. Regardless of training status, intramuscular triglyceride use accounted for about 90% of the oxidized fatty acids that were not supplied from adipose tissue via the plasma. Intramuscular triglycerides were the source of virtually all of the additional fatty acids oxidized in the trained state. Both before and after physical conditioning they explained the discrepancy between the rates of plasma FFA and total fat oxidation during moderate-intensity exercise of up to 2 hr in duration.